Legal phraseology within the context of Polish-German legal translation – a new monograph by Paweł Bielawski - Sekuła, Justyna Katarzyna (Comparative Legilinguistics, 2022)
The article attempts to provide a comprehensive assessment of the new monograph by Paweł Bielawski. For this purpose, the paper has been divided into four parts. The first part provides an introduction. The second part presents the theoretical basis, which the author of the monograph demonstrated in individual chapters. The third chapter assesses the monograph in terms of structure, editorial aspects and the compilation of literature. Finally, the last part is devoted to the possible addressees of the monograph and its advantages with regard to them.